2022
DOI: 10.3390/jcm11216261
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of the Modified Glasgow Prognostic Score in Urothelial Carcinoma: Outcomes from a Pooled Analysis

Abstract: Background: Many studies explored the prognostic value of the modified Glasgow Prognostic Score (mGPS) in urothelial carcinoma (UC), but the results are controversial. This study aimed to quantify the relationship between pretreatment mGPS and survival in patients with UC. Methods: A systematic literature search was conducted using Embase, PubMed, and Web of Science to identify eligible studies published before August 2022. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Tan et al included 13 studies involving 12,524 urothelial carcinoma patients and demonstrated that a high mGPS was obviously associated with poor OS (mGPS 0/1: HR = 1.33, P = .001; mGPS 0/2: HR = 2.02, P < .001) and PFS (mGPS 0/1: HR = 1.26, P = .021; mGPS 0/2: HR = 1.76, P = .013), recurrence-free survival (RFS) (mGPS 0/1: HR = 1.36, P < .001; mGPS 0/2: HR = 1.70, P < .001) and cancer-specific survival (mGPS 0/2: HR = 1.81, P < .001). [21] Besides, Wu et al [29,33,34,36,37] 1.81 0.96-3.41 .065 92.1 <.001 Japan 4 [30][31][32]35] 2.15 1.68-2.75 <.001 0.0 .953 Tumor stage Mixed 7 [29,30,33,34,[36][37][38] 1.77 1.20-2.63 .004 89.5 <.001 Extensive 3 [31,32,35] 2.37 1.57-3.58 <.001 0.0 .993 Treatment Mixed 3 [29,30,32] 2.66 1.59-4.46 <.001 57.4 .096 Chemotherapy 6 [31,[33][34][35][36][37] 1.68 1.00-2.82 .052 88.7 <.001 Comparison of mGPS mGPS 0 vs 1 5 [29,30,32,33,38] 1.31 1.16-1.49 <.001 0.0 .902 mGPS 0 vs 2 5 [29,30,32,33,38] 2.75 1.77-4.28 <.001 81.3 <.001 Progression-free survival 3 [31,34,35] 1.40 1.13-1.74 .002 ...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tan et al included 13 studies involving 12,524 urothelial carcinoma patients and demonstrated that a high mGPS was obviously associated with poor OS (mGPS 0/1: HR = 1.33, P = .001; mGPS 0/2: HR = 2.02, P < .001) and PFS (mGPS 0/1: HR = 1.26, P = .021; mGPS 0/2: HR = 1.76, P = .013), recurrence-free survival (RFS) (mGPS 0/1: HR = 1.36, P < .001; mGPS 0/2: HR = 1.70, P < .001) and cancer-specific survival (mGPS 0/2: HR = 1.81, P < .001). [21] Besides, Wu et al [29,33,34,36,37] 1.81 0.96-3.41 .065 92.1 <.001 Japan 4 [30][31][32]35] 2.15 1.68-2.75 <.001 0.0 .953 Tumor stage Mixed 7 [29,30,33,34,[36][37][38] 1.77 1.20-2.63 .004 89.5 <.001 Extensive 3 [31,32,35] 2.37 1.57-3.58 <.001 0.0 .993 Treatment Mixed 3 [29,30,32] 2.66 1.59-4.46 <.001 57.4 .096 Chemotherapy 6 [31,[33][34][35][36][37] 1.68 1.00-2.82 .052 88.7 <.001 Comparison of mGPS mGPS 0 vs 1 5 [29,30,32,33,38] 1.31 1.16-1.49 <.001 0.0 .902 mGPS 0 vs 2 5 [29,30,32,33,38] 2.75 1.77-4.28 <.001 81.3 <.001 Progression-free survival 3 [31,34,35] 1.40 1.13-1.74 .002 ...…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al included 13 studies involving 12,524 urothelial carcinoma patients and demonstrated that a high mGPS was obviously associated with poor OS (mGPS 0/1: HR = 1.33, P = .001; mGPS 0/2: HR = 2.02, P < .001) and PFS (mGPS 0/1: HR = 1.26, P = .021; mGPS 0/2: HR = 1.76, P = .013), recurrence-free survival (RFS) (mGPS 0/1: HR = 1.36, P < .001; mGPS 0/2: HR = 1.70, P < .001) and cancer-specific survival (mGPS 0/2: HR = 1.81, P < .001). [ 21 ] Besides, Wu et al also manifested that an elevated mGPS predicted poor OS in patients with pancreatic cancer (HR = 1.92, P = .002). [ 20 ] Tong et al enrolled 2691 patients from 15 cohort studies and indicated that mGPS was significantly associated with OS of renal cell carcinoma (mGPS 0/1: HR = 2.64, P = .002; mGPS 0/2: HR = 3.75, P < .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although meta‐analyses of the prognostic value of pretreatment GPS or mGPS in several cancer types have been reported, 30 , 31 , 32 , 33 , 34 no meta‐analysis has been reported for head and neck cancers. Furthermore, no meta‐analysis on the HS‐mGPS is available.…”
Section: Discussionmentioning
confidence: 99%